Herstory. The Value of Diaries as Sources for the Study of Women’s Independence Discourse: The Category of Viewpoint - Hawrysz, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The general aim of this outline is to indicate the diverse merits of women’s personal document literature for the study of women’s independence discourse. The specific objective is to identify the various points of view (understood as a linguistic category) that emerge in the texts regarding war and to reconstruct the image of war that emerges from the narratives of the female authors. Consequently, it can be said that the value of women’s personal document literature for researching women’s independence discourse is determined not only by its different perspective (presumably distinct from the male or official perspective) but also by the internal diversity within this discourse, which is connected to the broadly understood ideology.